Synthesis and characterisation of alternan-stabilised silver nanoparticles and determination of their antibacterial and antifungal activities against foodborne pathogens and fungi - Yilmaz, Mustafa Tahsin; Ispirli, Humeyra; Taylan, Osman; Dertli, Enes (ELSEVIER, 2020)
In this study, alternan isolated from Lactobacillus reuteri E81 was used as the stabilising agent to produce alternan-stabilised silver nanoparticles (AgNPs-Alt) and AgNPs-Alt were characterized and their antibacterial and antifungal activities were tested. The formation and the stability of AgNPs-Alt were determined by UV-vis spectroscopy analysis. SEM and TEM analysis revealed the uniform morphology of AgNPs-Alt with an average size of similar to 50 nm. The crystalline nature of the AgNPs-Alt was confirmed by XRD analysis. The interactions of alternan functional groups with silver was observed by FTIR analysis and thermal characteristics of AgNPs-Alt were determined by DSC analysis. Finally, the antibacterial and the antifungal activities of AgNPs-Alt were tested and AgNPs-Alt revealed inhibitory effects to pathogenic strains at 0.25 mg ml(-1) concentration and this activity was observed to be concentration dependent. For the antifungal activity, a higher level of AgNPs-Alt was required compared to the antibacterial activity.
Keywords: Alternan; Silver nanoparticles; Antibacterial; Antifungal; ANTIMICROBIAL ACTIVITY; GOLD NANOPARTICLES; GREEN SYNTHESIS; COPPER NANOPARTICLES; EXOPOLYSACCHARIDE; REDUCTION; CHITOSAN; BIOSYNTHESIS; ENHANCEMENT; PARTICLES; Food Science & Technology